Comparison Of Urban Sustainability Using Indicators Approach In The Cities Of Bahir Dar And Hawassa (Ethiopia) - K. Gashu (Geography, Environment, Sustainability, 2019)
Measuring urban sustainability remains an arena of dispute for long time. The promotion and development of urban sustainability are important to maximize the benefits of urbanization and minimize the negative externalities in urban environment and livelihoods. Each city has its strength and weakness towards sustainable urban development from different perspectives of various indicators. It is understood that assessment of sustainable city is related to identification and selection of sustainable development indicators. Therefore, in this research, we tried to develop a set of indicators, and indices for sustainability assessment in Bahir Dar and Hawassa cities in Ethiopia. The study focuses on the principal indicators, and an indicator framework has developed. The main purposes of sustainability indicators are to understand sustainability, supporting decisions, directing, involving stakeholders and empowerment. Twenty-six indicators with four main dimensions (economic, socio-cultural, environmental and institutional) have been identified. The computation of urban sustainability has to take into account all four dimensions equally. In the calculation of indicators, this study chooses a standard method [0, 1] using the minimum and maximum values for each indicator as an objective indicator. The sustainability indices calculated are 0.53 and 0.52 for Bahir Dar and Hawassa respectively, indicating that both cities have a moderate performance towards the development of a sustainable city. Aggregated data demonstrates that environmental indicators are moving towards sustainability, while economic, socio-cultural and institutional dimensions are performing relatively low in both cities, suggesting that sustainability studies need to work on all of sustainability dimensions that tend to better inform concerned bodies for policy intervention.